Ectopic fat: the true culprit linking obesity and cardiovascular disease? - Morelli, Mariangela; Gaggini, Melania; Daniele, Giuseppe; Marraccini, Paolo; Sicari, Rosa; Gastaldelli, Amalia (Thrombosis and Haemostasis, 2013)
Obesity is a major risk factor for cardiovascular disease and its complications. However, not all fat depots share the same characteristics. Recent studies have found that ectopic rather than subcutaneous fat accumulation is associated with increased cardiometabolic risk. However, ectopic fat accumulation can be seen initially as a protective mechanism against lipotoxicity. Subsequently the adipose tissue becomes dysfunctional, thus inducing systemic metabolic alterations (through release of cytokines) or specific organ dysfunctions. The purpose of this review is to summarise the current available data on the impact of excess adiposity vs ectopic fat in the development of cardiometabolic diseases.